Morrey Regularity of Solutions to Degenerate Elliptic Equations in Rn (Journal of Partial Differential Equations, 2003)
" In this paper, we study the Morrey regularity of solutions to the de- generate elliptic equation -(a_{ij}u_{xi})_{xj} = -(f_j)_{xj} in R^n. For this purpose, we introduce four weighted Morrey spaces in R^n."